How well does the Food Consumption Score capture diet quantity, quality and adequacy across regions in the Democratic Republic of the Congo (DRC)? - Marivoet, Wim; Becquey, Elodie; Van Campenhout, Bjorn (International Food Policy Research Institute, 2017)
This paper examined the ability of the FCS to capture variation in diet quantity and quality in different regions of the DRC; whether any change to the methodology of this food security indicator would structurally improve the correlation; and how well the WFP’s threshold reflects nutrient adequacy levels. For this validation study, we made use of 2004/5 HCES-DRC to derive the FCS and the benchmark variables against which the food proxy will be assessed.